Use of an in vivo system to determine the G418 resistance phenotype of bloodstream-form Trypanosoma brucei brucei transfectants - Murphy, N.B.; Muthiani, M.; Peregrine, A.S. (American Society for Microbiology, 1993)
We determined the level of susceptibility of Trypanosoma brucei brucei to the aminoglycoside G418 in vivo and demonstrated that it is possible to select for G418-resistant transfected T. brucei brucei bloodstream parasites in a mouse host by inoculating the drug intraperitoneally at doses between 40 and 80 mg/kg of body weight daily for 3 days. The ability to select for transfectants in vivo offers new possibilities for studies on genetic recombination in these parasites.